2019
DOI: 10.1039/c9en00408d
|View full text |Cite
|
Sign up to set email alerts
|

How reversible are the effects of silver nanoparticles on macrophages? A proteomic-instructed view

Abstract: Silver nanoparticles are known to have profounds effects on living cells, but little is known on how and to which extent cells recover after an acute exposure to silver nanoparticles. This is studied on macrophages in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 93 publications
(112 reference statements)
3
47
0
Order By: Relevance
“…Glutathione, a major cellular antioxidant, increased in response to sub‐toxic concentrations of both AgNPs and silver ions, agreeing with the results previously reported for AgNP/Ag + ‐treated keratinocytes and liver cells, as well as for macrophages exposed to silk nanoparticles . Previous proteomic studies of mouse macrophages have shown enzymes involved in glutathione biosynthesis to be induced in response to copper and silver nanoparticles, which was proposed to reflect upregulation of this pathway. The increase in glutamate excretion by AgNP‐exposed cells observed in the present study corroborates this hypothesis, as the cystine‐glutamate antiporter system, which provides cysteine for the rate‐limiting step of GSH synthesis, was reported to be activated in macrophages following pro‐inflammatory stimulation , .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Glutathione, a major cellular antioxidant, increased in response to sub‐toxic concentrations of both AgNPs and silver ions, agreeing with the results previously reported for AgNP/Ag + ‐treated keratinocytes and liver cells, as well as for macrophages exposed to silk nanoparticles . Previous proteomic studies of mouse macrophages have shown enzymes involved in glutathione biosynthesis to be induced in response to copper and silver nanoparticles, which was proposed to reflect upregulation of this pathway. The increase in glutamate excretion by AgNP‐exposed cells observed in the present study corroborates this hypothesis, as the cystine‐glutamate antiporter system, which provides cysteine for the rate‐limiting step of GSH synthesis, was reported to be activated in macrophages following pro‐inflammatory stimulation , .…”
Section: Discussionsupporting
confidence: 90%
“…An early work has shown that silver ions could inactivate yeast hexokinase due to binding with protein thiol groups, while a recent metallomics work has highlighted glycolytic enzymes as primary targets of ionic silver in E. coli . Additionally, similar findings, namely decreased activities of hexokinase and enolase, have been recently reported in mouse macrophages exposed to AgNPs . Hence, it is reasonable to postulate that silver‐induced downregulation of macrophage hexokinase, which catalyzes the first and rate‐limiting step of glycolysis, could possibly account for the observed changes in intracellular glucose and extracellular pyruvate.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the supernatant culture of cells exposed to NP and activated by LPS, the concentration of NO and cytokines such as interleukin 6 (IL-6), interleukin 10 (IL-10), monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor (TNFa) were measured as prevously described [34,38].…”
Section: No and Cytokines Productionmentioning
confidence: 99%
“…Visualization of F-Actin cytoskeleton was assayed by phalloidin staining according to previously published protocols [38][39][40] 2.8. Glutathione Assays Intracellular glutathione levels were assessed using the monochlorobimane technique, with some modifications [33].…”
Section: F-actin Stainingmentioning
confidence: 99%